AN ERROR ANALYSIS ON THE USE OF SIMPLE PRESENT TENSE IN PARAGRAPH WRITING OF THE SECOND SEMESTER AT ENGLISH LANGUAGE EDUCATION AT ISLAMIC UNIVERSITY OF OGAN KOMERING ILIR KAYUAGUNG - Arinta Perlin; Dewi Sartika; Ratna Nery (Edu-Ling: Journal of English Education and Linguistics, 2020)
The simple present tense is the most basic form that must be mastered by second-semester students of the Islamic University Ogan Komering Ilir Kayuagung. In addition, students are also required to write paragraphs using the simple present tense based on the syllabus. However, most students still have difficulty using the simple present tense in writing paragraphs. Therefore, the aim of this study was to identify the most dominant student errors in using the simple present tense. This research uses descriptive qualitative research methods. The research subjects involved the second-semester students of English Language Education at the Islamic University of Ogan Komering Ilir Kayuagung. The research instruments used a written test. Based on the calculation, it was found that 56.89% error of misformation, 15.51% error of addition, 13.79% error of omission, and 13.79% error of misordering made by the students.